Perception of smile attractiveness among laypeople and orthodontists regarding the buccal corridor space, as it is defined by the eyes. An innovated technique - YILMAZ, HANİFE NURAY (My University, 2023)
© 2023 Wiley Periodicals LLC.Objective: To investigate whether there is a relationship between the distance between the iris and pupil with the ideal size of buccal corridors. Materials and Methods: A full-portrait image of a male Caucasian was used to create a set of 11 digitally modified images with different buccal corridor space. A web-based cross-sectional study was designed and distributed via an online survey to 200 laypeople and 200 orthodontists to assess image attractiveness, using a Visual analogue scale. For the statistical analysis, Wilcoxon signed-rank and Mann–Whitney U tests were used. The significance level was set at p < 0.05. Results: The response rate for laypeople was 70% (n = 139), while the rate for orthodontists was 73% (n = 146). For the layperson group, the maximum smile attractiveness score was 10% of buccal width reduction, compared to the iris-pupillary distance, while for the orthodontists, it was 20%. The attractiveness of the smile was significantly reduced in both groups when the buccal corridor width was increased in comparison to the iris-pupillary distance. Conclusion: The length between the mesial part of the iris and the distal of the pupil, may constitutes a landmark for the estimation of the desired width of the buccal corridor. Clinical Relevance: Inter iris-pupillary distance can be the starting point in the smile designing process, in order to perform a facial driven selection of buccal corridor size.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; General Dentistry; buccal corridors; eyes; facial landmark; iris; smile attractiveness; smile design